Phagocytic activity of immunized-mouse peritoneal macrophages during Plasmodium berghei infection - Mahardika Agus Wijayanti, Mahardika Agus Wijayanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Macrophage represents one of the cellular component of the immune system which plays an important role during malarial infection. Both the number and functional activities including phagocyte activity of these cells increase during the infection.Objectives: This study was carried out to investigate the phagocyte activity of peritoneal macrophages from immunized and non-immunized mice during P. berghei infection.Methods: Swiss mice were divided into two groups, one experimental group was immunized by crude vaccine P. berghei, one control group was not immunized. Phagocyte activity was measured by the ability of mouse peritoneal macrophages to phagocytes latex particles in vitro.Results: In non-immunized mice the percentage of macrophages which were phagocyte latex particles was increased during early infection, reached a peak of about 9 times of the normal level then declined until the mice died. In the immunized mice this activity was increased to reach a peak of about 11 times of the normal level and remained high until recovery.Conclusion: Phagocyte activity of immunized-mice peritoneal macrophages was significantly higher than those of non immunized. The increase of the phagocyte activity seemed to be correlated with the ability of mice to overcome the infection.Key words : Immunization - P. berghei - Effector cells - Macrophages - Phagocytosis